An Analysis of the Influence of Lifestyle and Self-Control on Personal Financial Management - Fatimah Ayu Kurnia; Dea Indah Lestari; Fina Anggraini; Muhammad Aikal; Muhammad Irzaq Aufa Al-Fawwaz (Jurnal Pusat Manajemen, 2026)
The peak level of consumerism due to exposure to social media has made personal financial management a significant problem today. This research was conducted with the aim of evaluating the extent to which lifestyle and self-control affect the way a person manages their finances. Lifestyle plays a dominant role in curbing excessive spending tendencies, while self-control serves as the main foundation for planning for the future and suppressing unplanned purchases. To investigate the relationship between these factors, this study applied a quantitative methodology based on causal design. The data collection process relied on questionnaires distributed to students, given that this demographic is highly susceptible to external trends. Through its findings, this study is expected to offer a comprehensive perspective on the urgency of managing lifestyle and self-control in order to achieve personal economic stability in the future.